ANALISIS PERAN DILOMASI DIGITAL DALAM KOMUNIKASI INTERNATIONAL - Ahmad Saudi (Prodi Ilmu Komunikasi Universitas Putera Batam, 2021)
Abstract This study aims to find out how the role of digital diplomacy in international communication activities is carried out by international actors, namely the state. The development of technology and information affects the formation of digital society in the current era of globalization and is the basis for changing conventional forms of diplomacy in the direction known as digital diplomacy used in various countries. This study uses qualitative research methods with the technique of collecting reference sources of literature studies and data sources from books, journals, websites and newspapers that are relevant to the topic of this research. The results of this study show the important role of digital diplomacy by various countries in the process of international communication to achieve the goals of national interests namely politics, economy, education and security. Digital diplomacy has become an effective and efficient international communication tool so that international actors have begun to develop and implement it in their various diplomatic policies and activities. Keywords: Digital Diplomacy, International Communication, Globalization, Information Technology